Traumatismo e transmissão - Driga, Liana O. D (2018)
This dissertation aims at understanding the processes by which the descendants of survivors from social catastrophes work through their parent’s and grandparent’s traumatic experience. We search to enlighten how they dealt with the ruptures within transgenerational transmission, the effect of what was left untold and the resources they found to confront the silence of their elders and how they elaborated their traumatic inheritance. Due to the intimacy between the political and the psychic, we approach the importance of the collective dimension, the necessity of inscription of the experience in the social bond and the unfolding of narratives by the second and third generations. The object of our research was the possibilities of transmission, the ways by which the descendants recollect the experience of their elders into their own forms of narrative, which enables them to reinvent themselves through succesive generations. We then investigate the ways the untold or the unsaid operate and its varied impacts on the process of transgenerational transmission. We pursued clinical researches of different modalities of the unsaid/untold, first among the survivors of the Holocaust, then the struggles of a descendant of survivors from the Armenian genocide, as well as the problems of young men of Argelian descent in France facing the official silencing of French colonial power and its traumatic effects among the succeeding generations of Argelian immigrants. We also exploited a novel written by the daughter of a victim of the Ruandese genocide about her mother’s struggles to survive in exile prior to her murder and the massacre of her family. We also studied a daughter’s narrative of her mother’s diary as a survivor of Auschwitz. In this research we pursued three main guidelines: the rebonding of social relations, psychoanalytic transference and the addressment of ties with the other, and the importance of collective historical experiences and the underlying process of historicizing traumatic events, and finally the difficult process of distinguishing the meaning of erlebnis and experience in their long and necessarily incomplete elaboration of mourning